An Overview on Neurotoxic Pollutants by Biochemical Markers (International Journal of Innovative Research in Computer Science & Technology, 2022)
Neurotoxins produce molecular and  biochemical processes that suggest early-stage effects on  exposed people much before or below open illness  development. Studying these early occurrences may be a  legitimate way to create neurotoxicity indicators in those  exposed to chemical substances in the environment. Any use  of biochemical markers seems to be more difficult than in  other areas in neurotoxicology given the complex nature of  the function of both the central neural system, the multilevel  character of neurotoxic events and also the lack of access of  the objective tissue. Moreover, the evaluation of exposure,  subclinical effects and vulnerability to neurotoxic diseases  has been established in recent years. This article addresses  new biomarkers of neurotoxicity within occupational  medicine and its prospects and drawbacks.
Keywords: Biochemical; Biomarkers; Environment; Neurotoxic; Pollutants